Miejska Biblioteka Publiczna w Witnicy - w nowej starej siedzibie = The Municipal Public Library in Witnica - In a New Old Location - Wróblewski, Władysław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
As part of a recent revitalization, the Municipal Public Library in Witnica has returned to neoclassical architecture. It occupies a larger area than before and has gained a foyer and social facilities. On both sides of the library counter are the Children?s and Youth Section and the Adult Section. The children?s area features the Polish Fairy Tale Street, where the shelves are adorned with images of fairy tale characters. The adult section includes a lending area, reading room, and Regional Department. Two walls are decorated with photo wallpapers depicting scenes from Witnica in the early 20th century. The library has also been enhanced with professional sound equipment, an interactive board, and a multimedia projector.
Keywords: biblioteka; Witnica; regionalizm; bajka polska; teatrzyk lalkowy; library; regionalism; Polish fairy tale; revitalisation; puppet theatre